(3CSeGA GdLHGd hGdHbGY GdePchQI aj CTYGQ GdYQHs ((3WhGTi MSf GZG eDRjf s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf eG ai Ghdg GdgeRI CHh bHjS GdLHd GdeTQa Ydi GdUaG Sei HQLd ef ePML cGf jcfi HCHi bHjS dCfg Ghd ef Hfi ajg s
(3BNQgG (B:s
(3GdjeGeI HdO SejJ HGdRQbGA hcGf GSegG GdjeGeI Hjf YjQ HhGL jbGd dg MhQJGf hgj Gdjhe dfHi RjO GdehShi ef Hfi GdMSjf Je GdcJGH HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3gfGc fSNI CNQi GMOK ef gPg hHgG HjGV HQbe (B8 (3dZI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs